METHODOLOGY FOR TEACHING MEDICINAL PLANTS IN BOTANY LESSONS (Modern education and development, 2025)
This article discusses the role of medicinal plants in increasing students' interest in biology. At the same time, it highlights the idea of ​​cultivating qualities such as responsibility for nature conservation and a sense of responsibility for nature conservation in students through the cultivation of medicinal plants in an educational experimental plot.